Islamic Architectural Influence on Bajo Village Houses: A Case Study in Soropia Subdistrict, Southeast Celebes, Indonesia - Ahsan Hidayat Setiadi; Andi Al Mustagfir Syah; Nahdatunnisa Nahdatunnisa; M. Arzal Tahir (Journal of Islamic Architecture, 2026)
This study aims to analyze the influence of Islamic architectural principles on the design of traditional houses of the Bajo tribe in Bajo Village, Soropia Subdistrict, Southeast Sulawesi. Using a descriptive-analytical method, data were collected through direct observation, in-depth interviews, and document analysis. The study involved 123 traditional Bajo houses categorized into three types: water-based, semi-water-based, and land-based. Key architectural elements, including building orientation, spatial layout, use of building materials, and roof and foundation design, were examined. The findings reveal that the orientation of Bajo houses towards the Qibla is influenced by Islamic teachings, particularly in QS. Al-Baqarah 2:143, while privacy and simplicity in spatial arrangement are aligned with QS. An-Nur 24:27-28 and QS. Ar-Rum 30:41. Islamic spiritual values are also reflected in the design of roofs and foundations, symbolizing the greatness of Allah and the balance of life as stated in QS. Al-Baqarah 2:255 and QS. Al-Hujurat 49:9. This research highlights the significance of integrating Islamic values in architectural practices, especially in preserving traditional Bajo houses, which serve not only as dwellings but also as transmitters of religious and cultural values. The study offers new insights into the relationship between religion, culture, and architecture in a local context, while providing practical guidance for the preservation and development of traditional architecture amidst modernization.